Provider Attitudes, Experiences, and Practices on Childbirth Education and Birth Plans [39M]. (May 2017) - Afshar, Yalda; Fahey, Jacqueline; Mei, Jenny; Saeb, Samia; Gregory, Kimberly D.
Abstract : INTRODUCTION: Attendance at childbirth education classes (CBE) has declined, while the rate of birth plans has increased. We sought to describe the perception and practices of obstetric providers on CBE and birth plans. METHODS: A national online-survey was distributed through professional societies and social-media. We collected provider and patient demographics, practice-settings, and perceptions. Responses were on a Likert scale from 1 (not important) to 5 (very important). RESULTS: Of 567 eligible surveys, 75.7% were physicians. This cohort believed prenatal care (mean ± SD, 4.4±0.9) and CBE (3.6±1.0) are predictors of patient satisfaction. Most providers routinely recommend (69.7%) and have favorable views on CBE (84%). They had neutral views on doulas (2.9±1.2). With increasing age, providers were more likely to recommend CBEs (0.159, p=0) and birth plans (0.174, p=0). Increasing provider age correlated with believing that prenatal care (0.111, p=0.01), CBE (0.190, p=0) and birth plans (0.108, p=0.012) were predictors of satisfaction and favorable obstetrical outcomes (0.149, p=0.001). Only 26% of providers had favorable views on birth plans and most providers (66.5%) did not recommend birth plans and 31% felt they were predictors of poor obstetrical outcomes. Increasing practice-years correlated with favorable views on CBEs (0.167, p=0) and birth plans (0.205, p=0). Providers with higher obstetrical clinical volume more likely recommend birth plans (0.118, p=0.009). CONCLUSION: Providers view CBE as an important predictor of patient satisfaction while they have unfavorable view of birth plans. Further research is needed to understand how to improve childbirth related patient satisfaction and birth experience.